Scientific Advice for Policy in France (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The concept of a “science for policy ecosystem” is increasingly being used at the European Commission’s Joint Research Centre, and has been operationalized in a series of reports on several European countries, published in 2021-2022. Using an original methodology developed in one of these reports, this paper describes the French science for policy ecosystem, focusing on the scientific advisory bodies for environmental and public health matters. Beyond this specific case study, the paper reflects on the theoretical and methodological implications of the concept, in the light of the literature in Science and Technology Studies (STS) and in policy sciences.
Keywords: science for policy ecosystem; public health; environment; advisory science; public policy